Clinical treatment of a leg problem in an adult bull elephant - Donald Mpanduji; R. Mdegela; E. Batamuzi; M. Mtambo; S. Bittegeko (Pachyderm)
Leg problems are not uncommon in free ranging elephants, but little has been recorded on the factors behind them i.e. natural or hunting injury, deformity, disease etc. This article describes the veterinary services rendered to an emaciated adult bull with a swollen foreleg which was tentatively diagnosed as evidence of chronic arthritis. The animal was given both antibiotics and anti-inflammatory drugs suggested for foot pathology. Ten days after treatment the animal was foraging and moving back and forth from a local waterhole area . The bull's gait certainly improved, however further analysis was not possible as the animal disappeared soon after.